Coronary embolism resulting in myocardial infarction: diagnosis and treatment - Shufu Chang; Rende Xu; Yuxiang Dai; Chenguang Li; Hao Lu; Qing Qin; Jianying Ma; Juying Qian; Junbo Ge (European Journal of Medical Research)
Abstract Background Coronary embolism (CE) is rare and is an unusual cause of acute myocardial infarction (AMI). Japan NCVC criteria of CE were the first criteria that did not be verified and accepted. Methods We collected all the CE patients in our hospital between 2015 and 2021, analyzed the characters, diagnosis, and treatment, and confirmed the value of Japan NCVC criteria. Results Eighteen AMI patients diagnosed with CE were enrolled. Seventeen patients (94.4%) were given PCI treatments. Six patients (33.3%) had artificial heart valves, and three (16.7%) had mechanical valves. Eleven patients (61.1%) had atrial fibrillation (AF), one (5.6%) had hypertrophic cardiomyopathy, and two (11.1%) had hypercoagulable state. 68.8% of patients had insufficient anticoagulation in this study. Seven patients (38.9%) fulfilled the criteria for definite CE, and nine (50%) were classified as probable CE. The other two patients (11.1%) did not fulfill the criteria of CE with distal coronary artery embolism and one criterion of Japan NCVC criteria. The diagnosis accuracy rate of Japan NCVC criteria was 88.9%. Thrombus aspiration was the first-line treatment used in 14 patients (77.8%) and performed in 9 vessels (47.4%) as the only treatment method. Conclusions CE is rare in AMI, and AF is the most critical cause which should draw our attention. The Japan NCVC criteria were a helpful diagnostic tool for CE with high accuracy, but the distal coronary artery embolism with moderate atherosclerosis might be overlooked. Thrombus aspiration was the preferred treatment to remove thrombus and restore coronary flow to improve prognosis.